The Impact of Technology on Halal Certification Intentions of MSMEs: A Gender-Based Analysis - Yan Putra Timur; Ririn Tri Ratnasari; Anwar Allah Pitchay; Usman Jamilu; Dyah Permata Sari; Firdan Thoriq Faza; Muhammad Rifqi (AL-MUZARA'AH, 2025)
This study aims to identify the main determinants influencing MSMEs in applying for halal certification through digital media, using a combination of the DeLone & McLean and UTAUT models, with a comparison between male and female MSME owners. The PLS-SEM Multi-Group Analysis (MGA) approach was employed as the evaluation method in this quantitative study, using SmartPLS 3.0. A total of 300 respondents met the required criteria. The findings show that service quality is not a major determinant for the male group. On the other hand, for the female group, system quality does not significantly influence intention to apply halal certificate. Several other constructs, such as performance expectancy, effort expectancy, social influence, and information quality, show similar results across both groups, while facilitating condition does not have a significant impact on either male or female groups. These findings provide practical implications, particularly for policymakers. The government should improve performance, ease of use and information clarity for MSMEs. For male MSMEs, focus on system quality and customer support, while for female MSMEs, extension officer assistance would be more effective in encouraging halal certificate applications.